Konsentrasi Bunuh Minimal (KBM) Ekstrak Propolis Lawang terhadap Candida albicans - Alvita Wibowo; Ira Widjiastuti; Widya Saraswati (Conservative Dentistry Journal, 2017)
Background: Candida albicans is the most resistant fungi in root canals. The existence of Candida albicans after root canal treatment can cause the failure of root canal treatment. The prevalence of this case is 36,7%. Propolis is a resinous substance which has many pharmaceutical and biological effects such as antimicrobial activities. Its active components include flavonoid, saponin, and tannin, have an important role in antimicrobial activities. In this study, antifungal aspect of propolis extract was investigated. Purpose: The aim of this study was to determine the minimum fungicidal concentration (MFC) of propolis extract againts Candida albicans. Methods: This research was a laboratory experimental study. Propolis extract produced by propolis farm from Lawang. The antifungal activity test was performed by colony counting fungi in sabouraud’s dextrose agar (SDA) to determine the value of MFC of propolis extract againts Candida albicans. Result: At the concentration of 72,5%, 73,5%, 74,5%, 75,5%, 76,5%, and 77,5% there are decreases in the number of Candida albicans fungal colonies when compared with positive control group. There are significant differences in each study group (p<0,05). At the concentraion  of 76,5% was not revealed any fungal growth of Candida albicans, it was because the antifungal effect of propolis extract has reached MFC. Conclusion: The minimum fungicidal concentration of propolis extract againts Candida albicans is 76,5%.